The Qur'anic Perspective On Marine Resource Conservation: A Human Responsibility - Ulya, Miftah; Sukiyat, Sukiyat; Yasir, Muhammad; Nurliana, Nurliana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The conservation of marine resources is an important issue in maintaining the balance of ecosystems and the sustainability of life on earth. The Qur'an provides clear guidance on human responsibility in protecting nature, including marine resources. This article seeks to reveal the messages contained in the Qur'an related to the ocean. The Qur'an emphasises the importance of maintaining the balance of nature (mizan) and prohibits destruction (fasad) on earth. QS. Al-A'raf [7:56] and QS. Al-Baqarah [2:30] emphasise the role of humans as khalifahs responsible for environmental sustainability. These principles include the protection of marine resources through conservation measures and sustainable management. Therefore, a friendly attitude towards the environment and sustainable utilisation is a shared responsibility. This research was conducted through a literature study using qualitative, descriptive methods, relying on deductive and inductive approaches and then analysed structurally and sociologically ethnographically. These findings underscore that marine resource conservation in Islam is not only an ecological obligation but also a rewarding act of worship. Implementing these principles in everyday policies and practices can help address global environmental challenges and ensure the sustainability of marine resources for future generations. The Qur'anic perspective on marine resource conservation emphasises human responsibility for maintaining the balance of nature and preventing damage. These principles are relevant to be applied in modern conservation efforts to achieve environmental sustainability